ISOTOPIC SYSTEMATICS OF PRESOLAR SILICON CARBIDE FROM THE ORGUEIL (CI) CHONDRITE: IMPLICATIONS FOR SOLAR SYSTEM FORMATION AND STELLAR NUCLEOSYNTHESIS - Huss G.R.; Hutcheon I.D.; Wasserburg G.J. (My University, 1997)
One hundred and forty individual SiC grains (1-9.6 μm) and twenty-two grain aggregates (2.3-7.8 μm) from the Orgueil (CI) chondrite have been measured by ion microprobe. Silicon and carbon isotopic data were obtained for all individual grains and aggregates, and nitrogen, magnesium, and aluminum abundances and isotopic compositions were measured for most grains and aggregates. Abundances of lithium, beryllium, boron, and sodium were measured for some individual grains. Orgueil SiC is remarkably similar to Murchison K-series SiC in the ranges and distributions of silicon and carbon isotopic compositions, the initial abundances of 26Al, the abundances of minor and trace elements, and the proportions of isotopically unusual grains. Higher 15N/14N ratios in 1-4 μm Murchison K-series SiC grains relative to similar-sized Orgueil grains are inferred to be due to higher amounts of terrestrial nitrogen in the Murchison samples. Higher 15N/14N ratios in 3-6 μm Murchison KJH SiC grains cannot be explained by terrestrial nitrogen and imply that larger SiC grains sampled a different population of parent stars. SiC aggregates have different average silicon and carbon compositions than individual grains, indicating different source stars for the 0.1-1 μm constitutent grains. However, the aggregates probably formed by clumping of small grains during laboratory procedures, not at the stellar source. Differences between Murchison L-series SiC and SiC from Murchison K-series and Orgueil are due to the presence of terrestrial SiC among L-series grains and to the larger average grain size of L-series SiC. When terrestrial contamination, sample size, and grain size are taken into account, there is no evidence of an intrinsic difference between Orgueil and Murchison SiC.The Orgueil data provide new information about stellar nucleosynthesis and the SiC parent stars. Carbon and nitrogen isotopic compositions indicate that nuclear processing in addition to that described by most stellar models occurs below the convective stellar envelope during the Red Giant and AGB phases (Cool Bottom Processing). Grains with high 15N/14N but with other characteristics consistent with AGB source stars indicate that 15N is produced in AGB stars, contrary to the predictions of the standard models. A significantly higher rate for the 18O(α, n) 15N reaction than is typically used might reconcile the models with the observations. No data currently rule out a higher reaction rate. Addition of 18O produced via 14N (α, γ) 18O below the hydrogen shell and burned to 15N in the envelope may also play a role in producing the high 15N/14N ratios observed in some SiC grains. Following previous workers, we take the slope #2.2 silicon isotope array defined by mainstream SiC grains to reflect the initial compositions of the parent stars due to galactic evolution. A general correlation between 12C/13C and 29,30Si/28Si and more scatter around the silicon array at low 29,30Si/28Si indicate that SiC grains with higher 29,30Si/28Si ratios come from higher-metallicity parent stars. A lack of resolved isotopic effects in in 25Mg/24Mg suggests that variations in initial magnesiumcompositions of the parent stars are at least a factor of three smaller than those in silicon and that the 22Ne neutron source was not significantly activated in the AGB stars that produced SiC grains, in accord with theory. These observations indicate that the parent stars of most mainstream SiC grains were =<2.3 M# and experienced enough Third Dredge-up thermal pulses to supply their envelopes with 2-3% helium shell material. A few grains have characteristics suggesting that they came from more-massive stars. Most parent stars of >1 μm SiC grains apparently had metallicities higher than that of the sun.